2017
DOI: 10.1016/j.jfma.2016.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical approach affects intraocular lens decentration

Abstract: Scheimpflug imaging can be used as a quantitative tool to evaluate IOL position. The incision site affected the IOL position, this finding was significant at 1 week postoperatively only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Nonetheless, the minimal tilt and decentration values reported in this study with the pupillary axis as reference point are in line with the values described in the literature. 26 Furthermore, similar to Baumeister et al, we found that IOL tilt and decentration were stable over time 29 suggesting a good capsular bag stability of the Aspira-aXA likely due to its unique design. We also did not notice differences in tilt and decentration values between eyes with different axial lengths.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Nonetheless, the minimal tilt and decentration values reported in this study with the pupillary axis as reference point are in line with the values described in the literature. 26 Furthermore, similar to Baumeister et al, we found that IOL tilt and decentration were stable over time 29 suggesting a good capsular bag stability of the Aspira-aXA likely due to its unique design. We also did not notice differences in tilt and decentration values between eyes with different axial lengths.…”
Section: Discussionsupporting
confidence: 83%
“…Despite these difficulties in data comparison, it has been shown that decentration up to 0.40 mm and tilt up to 7.0 degrees do not influence visual performance. 26,27 According to modern schematic model eyes (e.g. the Liou-Brennan eye) the crystalline lens is tilted and decentered.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported an appearance of astigmatism and Higher Order Aberrations (HOAs) such as coma with IOL misalignment [4] and tilt [25,26]. IOL stability inside the eye is influenced by many factors such as the capsular bag diameter related to the IOL overall diameter [27], the haptic design and lens material [7], the surgical technique [28], and even some postoperative actions like the Nd:YAG laser application for posterior capsulotomy [29].…”
Section: Plos Onementioning
confidence: 99%